NN-DataHub: Database for Neurological Monitoring and Multimodal Correlation in Neonatology - Seabra, João; Leão, Richardson N. (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2025: Companion Proceedings of the 21st Brazilian Symposium on Information Systems, 2025)
This study proposes the development of a structured database for the storage and analysis of biomedical data from newborns in neonatal intensive therapy units, with an emphasis on neurophysiological signals such as electroencephalography (EEG) and near-infrared spectroscopy (NIRS). Alongside EEG/NIRS, the database will be designed to integrate other physiological parameters such as heart and respiratory rates, peripheral oximetry, motor behavior and reflexes, in addition to clinical/laboratory data, allowing for the correlation between different variables and the early identification of neonatal neurological injuries. The proposed system is intended for clinical use and could be an important tool in research, promoting a more integrated and predictive approach to neonatal monitoring.